Cattle manure management using microbial fuel cells for green energy generation. (24th September 2021) - Syed, Zainab; Sonu, Kumar; Sogani, Monika
Abstract: The increased use of estrogens in modern livestock farming has caused them to enter the environment and they have become a serious human health concern. Studies have suggested that animal waste treatment using bio‐electrochemical systems may reduce their environmental impact. Bio‐electrochemical systems hold great potential as green bioenergy conversion systems utilizing different bio‐wastes as the feedstock. The present work involves the development of a laboratory‐scale microbial fuel cell (MFC) for energy generation from two different cattle manures (cow dung and buffalo dung) as bio‐waste after ultrasonication pretreatment for a period ranging from 4 to 8 min. The maximum power density in both the cattle manures is reported with 5.5 min of ultrasonication pretreatment at 40 kHz, 120 W, at 25 °C. Two similar setups of a single‐chambered membrane‐less MFC were fed with pretreated cow dung (PCD) and pretreated buffalo dung (PBD) as substrates in the anodic chamber, and the effects of various parameters such as temperature and time were investigated. The maximum chemical oxygen demand and biochemical oxygen demand removal were 80% and 87% respectively, with PBD. The coulombic efficiency of PBD‐MFC was slightly higher (0.53%) than that of PCD‐MFC (0.48%). The maximum voltage (0.65 V) and power density (12.75 mW m −2 ) were also recorded with PBD‐MFC. Energy recovery was also studied by electrically stacking five individual units of these MFCs into series and parallel arrangements. The parallel and series PBD‐MFC stacks yielded 22 and 12 times higher power output respectively than the individual unit. © 2021 Society of Chemical Industry and John Wiley & Sons, Ltd